(untitled) (Ibrahim Medical College Journal, 2015)
Melioidosis, caused by Burkholderia pseudomallei, is a potentially fatal infectious disease. Early and correct diagnosis is important, as mortality in untreated melioidosis is high. The first case of melioidosis from Bangladesh was reported in 1988. Since then a few cases have been reported from Bangladesh. We report here four culture confirmed cases of melioidosis diagnosed in BIRDEM Genaral Hospital during May 2009 to April 2010.The detail demographic data, clinical features and outcome are discussed. We have also reviewed all the melioidosis cases among Bangladeshi population recorded from 1988 to 2014. Ibrahim Med. Coll. J. 2014; 8(1): 25-31